Severe pulmonary tuberculosis with organizing pneumonia: a diagnostic ambiguity - Mohammad, Nurashikin; Che Rahim, Mohd Jazman; Wan Ahmed, Wan Aireene; Wan Ghazali, Wan Syamimee (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2021)
Pulmonary TB may present insidiously and ambiguously, leaving clinicians with a diagnostic dilemma. A 30-year-old lady with underlying spinocerebellar ataxia presented with progressive shortness of breath, prolonged cough with whitish sputum, loss of appetite and weight loss of 1-year duration. Physical examination showed a cachectic, tachypnoeic female with finger clubbing and coarse crepitations on lung auscultation. Chest radiograph showed bilateral air space opacities relatively sparing the upper zone. Contrast-enhanced CT thorax revealed bilateral cavitary necrotising consolidations, multiple scattered lung nodules with surrounding ground-glass opacities. After exclusion of alternative diagnoses, cryptogenic organizing pneumonia diagnosis was made. She had a rapid clinic improvement once steroid was started. TB polymerase chain reaction (PCR) from bronchoscopic bronchial washing eventually was positive. Anti-TB treatment was started, and oral steroid was slowly tapered down. Organizing pneumonia (OP) may complicate pulmonary TB. Diagnosing OP without lung biopsy requires a multi-disciplinary approach, taking into consideration all available evidences. Early steroid therapy is lifesaving and should be considered after thorough exclusion of alternative diseases.